Effect of dual task on balance in older adults with mild cognitive impairment - Kedkanok Srimaloon; Patima Silsupadol; Somporn Sungkarat (Journal of Associated Medical Sciences, 2017)
Background: Balance impairment is an important risk factor for falls and is associated with cognitive impairment. However, it is inconclusive whether older adults with mild cognitive impairment (MCI) have impaired balance. This may be due to the balance tests commonly used in clinical settings are not physically and/or cognitively challenged enough to identify balance impairment in this population.